2021
DOI: 10.3390/antiox10081268
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin Alleviates AflatoxinB1-Induced Apoptosis and Oxidative Stress in the Liver of Mice through Activation of Nrf2 Signaling Pathway

Abstract: Aflatoxin B1 (AFB1), a threatening mycotoxin, usually provokes oxidative stress and causes hepatotoxicity in animals and humans. Luteolin (LUTN), well-known as an active phytochemical agent, acts as a strong antioxidant. This research was designed to investigate whether LUTN exerts protective effects against AFB1-induced hepatotoxicity and explore the possible molecular mechanism in mice. A total of forty-eight mice were randomly allocated following four treatment groups (n = 12): Group 1, physiological saline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 60 publications
1
34
0
Order By: Relevance
“…Caspase-3 is activated into an activated form by proteolysis under the stimulation of a variety of apoptotic signals and then participates in apoptotic processes. 37 Here, we found that the ratio of Bcl-2/Bax was decreased, and the caspase-3 protein was increased by CP. Therefore, TSP inhibited the CP-induced intrinsic apoptosis in ovarian granulosa cells via keeping pre-existing Bcl-2 protein and inhibiting Bax overexpression, which in flip can suppress caspase-3 expression.…”
Section: Discussionmentioning
confidence: 66%
“…Caspase-3 is activated into an activated form by proteolysis under the stimulation of a variety of apoptotic signals and then participates in apoptotic processes. 37 Here, we found that the ratio of Bcl-2/Bax was decreased, and the caspase-3 protein was increased by CP. Therefore, TSP inhibited the CP-induced intrinsic apoptosis in ovarian granulosa cells via keeping pre-existing Bcl-2 protein and inhibiting Bax overexpression, which in flip can suppress caspase-3 expression.…”
Section: Discussionmentioning
confidence: 66%
“…AFB1 is the most toxic of many secondary metabolites produced by fungi, posing considerable health risks to people and animals due to its hepatotoxic, immunotoxic, carcinogenic, and teratogenic effects [ 30 , 31 , 32 ]. The role of oxidative stress associated with AFB1-mediated organ toxicity has been widely researched in animal models [ 11 , 33 , 34 ]. Among these studies, a great deal of attention has been devoted to the liver, which is the principal organ for AFB1 bioactivation.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the kidney is also involved in the accumulation of toxin AFB1. Research has demonstrated that oxidative stress is a critical risk factor for AFB1 toxicity and that exposure to AFB1 raises contents of reactive oxygen species (ROS), which can impair cellular redox homeostasis, leading to oxidative stress-induced kidney injury [ 11 ]. Therefore, mitigation of oxidative stress is emphasized as an effective strategy to treat AFB1 nephrotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…It also was reported that luteolin activates the Nrf2 pathway. For example, luteolin enhanced autophagy and antioxidative processes in both in vivo and in vitro models of intracerebral hemorrhage [ 32 ], protected heart tissues in STZ-induced diabetic mice through modulating Nrf2-mediated oxidative stress and NF- κ B-mediated inflammatory responses, and alleviates aflatoxin B 1 -induced apoptosis and oxidative stress in the liver of mice through activation of the Nrf2 pathway [ 33 ]. The current results showed that luteolin promoted nuclear translocation of Nrf2, upregulated the expressions of HO-1 and NQO-1, increased the activities of SOD and GSH-PX, and decreased intracellular levels of ROS and MDA, suggesting that luteolin activated the Nrf2 pathway, thereby improving the survival rate of oxidative damaged ARPE-19 cells.…”
Section: Discussionmentioning
confidence: 99%